High-energy-storage-density anti-ferroelectric ceramic material and preparation method thereof
By adding directionally arranged Al2O3 sheet templates to antiferroelectric ceramic materials and grinding and gold spraying, the problem of low energy storage density of existing antiferroelectric ceramic materials is solved, and high breakdown strength and high The effect of energy storage density.
Patent Information
- Application Number
- CN202410727274.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-06
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-06-06
AI Technical Summary
The existing antiferroelectric ceramic materials have low energy storage density and are limited in their application in the field of energy storage dielectrics due to insufficient breakdown strength.
By adding Al2O3 sheet templates to the ceramic substrate and arranging them in a direction in the same direction through casting preparation process, combining polishing and gold spraying treatment, the Al2O3 sheet templates are arranged parallel to the test electrode, thereby improving the impact of the material Wear strength and energy storage density.
The breakdown strength and energy storage density of antiferroelectric ceramic materials are significantly improved, meeting the application needs of higher energy storage density, while maintaining the antiferroelectric characteristics of the material.
Smart Images

Figure CN119490361A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of functional materials, and in particular to an antiferroelectric ceramic material with high energy storage density and a preparation method thereof. Background Art
[0002] Dielectric capacitors have the advantages of high power, good density, reliability and ultra-fast charge and discharge rates, and are widely used in modern scientific and technological fields such as electronic communications, automobiles, military industry and aerospace. However, the existing energy storage dielectric materials have problems such as low energy storage density, low energy storage efficiency and small discharge current, which cannot meet the needs of the development of current electronic devices. Antiferroelectric materials have better energy storage performance than other dielectric materials because of their almost zero residual polarization intensity and extremely high polarization intensity. However, due to their low breakdown strength, the energy storage density is low, which greatly limits their application in the field of energy storage dielectrics. Therefore, studying dielectric materials with high breakdown strength and high energy storage density is the key to expanding their application areas.
[0003] Adding a high-insulation material reinforcement phase with the characteristics of low dielectric constant, low dielectric loss, wide bandgap and high breakdown strength to a ceramic matrix, the resulting composite material can simultaneously obtain the characteristics of the matrix and the reinforcement phase, and even obtain advantages that neither of them has. The high-insulation material reinforcement phase is compounded with the ceramic matrix phase, while improving the dielectric breakdown strength, it will not significantly change the electrical properties of the matrix ceramic, and finally obtain a composite ceramic dielectric material with better performance. Most of the high-insulation material reinforcement phases added to the ceramic matrix in the prior art are granular. Due to the shape and orientation of the reinforcement phase, the effect of enhancing the breakdown strength is not obvious, resulting in its energy storage density being difficult to meet application requirements. Therefore, it is of great significance to study the shape and orientation of the added high-insulation material reinforcement phase in the ceramic matrix to effectively improve the breakdown strength of the antiferroelectric ceramic material, and induce a higher polarization strength through a high electric field, thereby effectively improving the energy storage density of the antiferroelectric ceramic material.
[0004] Inventive content
[0005] The purpose of the present invention is to provide an antiferroelectric ceramic material with high energy storage density and a preparation method thereof. The antiferroelectric ceramic material has a high insulation material reinforcement phase Al2O3 sheet template added thereto which is oriented and arranged in the same direction in the ceramic matrix and is parallel to the test electrode, and has extremely high breakdown strength and energy storage density.
[0006] In order to achieve the above object, the technical solution of the present invention is:
[0007] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn0.3 ) 0.995 O3 - x wt% Al2O3, where 0 < x ≤ 0.7, preferably, 0.1 ≤ x ≤ 0.7. Al2O3 is a flaky template, and the Al2O3 flaky templates are oriented in the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flaky templates are regulated to be parallel to the test electrodes by polishing and spraying gold on the upper and lower surfaces parallel to the Al2O3 flaky templates.
[0008] A preparation method of a high energy storage density antiferroelectric ceramic material, comprising the following steps:
[0009] S1: According to the stoichiometric ratio of the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - x wt% Al2O3, prepare the powder raw materials of PbO, La2O3, ZrO2, and SnO2 in proportion. Put the powder raw materials, anhydrous ethanol solvent, and yttria-stabilized zirconia bead milling medium into a ball mill for ball milling, then dry and screen to obtain a mixed powder. Calcinate the mixed powder in a high-temperature furnace to synthesize (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 solid solution powder, that is, obtain PLZS solid solution powder;
[0010] S2: Add anhydrous ethanol solvent and yttria-stabilized zirconia bead milling medium to the PLZS solid solution powder obtained in step S1, then ball mill, dry, and screen to obtain PLZS fine powder;
[0011] S3: Add anhydrous ethanol solvent, butanone solvent, triethyl phosphate dispersant, polyvinyl butyral binder, dibutyl phthalate plasticizer, and yttria-stabilized zirconia bead milling medium to the PLZS fine powder obtained in step S2, and then ball mill to obtain a ceramic slurry;
[0012] S4: According to the stoichiometric ratio of the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - x wt% Al2O3, proportionally add Al2O3 flaky templates, and then stir in a magnetic stirrer to obtain a mixed slurry;
[0013] S5: Use a vacuum degassing machine to degas the mixed slurry obtained in step S4 through stirring and vacuum pumping;
[0014] S6: casting the mixed slurry obtained in step S5 by a manual casting machine, so that the Al2O3 sheet template is oriented in the same direction in the high energy storage density antiferroelectric ceramic material matrix by casting, and then drying and cutting to obtain a ceramic diaphragm;
[0015] S7: Laminating the ceramic diaphragm obtained in step S6 in a high energy storage density antiferroelectric ceramic material matrix according to an Al2O3 sheet template and placing it in a mold, heating the mold by a heating sleeve, hot pressing by a manual tablet press, compacting by a cold isostatic press, and then manually cutting to obtain a ceramic green embryo;
[0016] S8: placing the ceramic green body obtained in step S7 in a muffle furnace for debinding and sintering to obtain a sintered ceramic sheet;
[0017] S9: polishing and ultrasonically cleaning the upper and lower surfaces of the sintered ceramic sheet obtained in step S8 that are parallel to the Al2O3 sheet template, and drying them, spraying gold on the upper and lower surfaces that are parallel to the Al2O3 sheet template, to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged in parallel.
[0018] Preferably, in step S7, the ceramic diaphragms obtained in step S6 are stacked and arranged in the same direction according to the Al2O3 sheet template, and then placed in a mold, the mold is heated by a heating sleeve, hot pressed by a manual tablet press, compacted by a cold isostatic press, and then manually cut to obtain a ceramic green body.
[0019] Preferably, in step S4, the ceramic slurry obtained in step S3 is placed in a beaker, a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-xwt%Al2O3 is prepared, and Al2O3 flake template is added in proportion. The mass of the Al2O3 flake template added is xwt% of the mass of the PLZS fine powder in step S2. Then the beaker is placed in a magnetic stirrer and stirred at a speed of 450-600r / min and a stirring time of 24-36h to obtain a mixed slurry.
[0020] Preferably, in step S1, the mass ratio of anhydrous ethanol solvent to powder raw material is (0.8-0.9):1, the mass ratio of yttrium-stabilized zirconia beads to powder raw material is (4.5-3.5):1, the ball mill speed is 280-300r / min, the ball milling time is 12-24h, and then the mixed powder is obtained after drying and sieving, and the mixed powder is calcined in a muffle furnace at 800°C for 2h to synthesize PLZS solid solution powder.
[0021] Preferably, in step S2, the mass ratio of anhydrous ethanol solvent to PLZS solid solution powder is (0.8-0.9):1, the mass ratio of yttrium-stabilized zirconia bead ball milling medium to PLZS solid solution powder is (4.5-3.5):1, the ball milling speed is 280-300 r / min, the ball milling time is 24-36h, and then drying and sieving to obtain PLZS fine powder.
[0022] Preferably, in step S3, the mass ratio of anhydrous ethanol solvent to PLZS fine powder is (4-5):10, the mass ratio of butanone solvent to PLZS fine powder is (3-4):10, the mass ratio of triethyl phosphate dispersant to PLZS fine powder is (0.2-0.4):10, the mass ratio of polyethanol butyral adhesive to PLZS fine powder is (0.6-0.7):10, the mass ratio of dibutyl phthalate plasticizer to PLZS fine powder is (0.6-0.7):10, the mass ratio of yttrium stabilized zirconia beads to PLZS fine powder is (4.5-3.5):1, the ball milling speed is 280-300r / min, and the ball milling time is 24-36h.
[0023] Preferably, in step S4, the mass of the added Al2O3 flake template is (0.1-0.7)% of the mass of the PLZS fine powder in step S2, the stirring speed of the magnetic stirrer is 450-600 r / min, and the stirring time of the magnetic stirrer is 24-36 h.
[0024] Preferably, in step S5, the defoaming time of the vacuum defoamer is 1-2 hours, and the stirring speed is 150-350 r / min.
[0025] In the above technical scheme, the high energy storage density antiferroelectric ceramic material and the preparation method thereof of the present invention have the following beneficial technical effects:
[0026] (1) The Al2O3 sheet template is first prepared by a molten salt method and then tape-casted (also called scraper forming) by a tape-casting preparation process. The tape-casting preparation process can make the Al2O3 sheet template oriented in the same direction in the antiferroelectric ceramic material matrix. Then, by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 sheet template, an antiferroelectric ceramic material in which the Al2O3 sheet template and the test electrode are arranged in parallel is obtained, so that the Al2O3 sheet template effectively disperses the applied electric field in the entire antiferroelectric ceramic material matrix to reduce the uneven distribution of the local electric field, which is beneficial to improve the breakdown strength of the antiferroelectric ceramic material, and then improve the energy storage density of the antiferroelectric ceramic material.
[0027] The existing granular Al2O3 reinforcement phase has a small width-to-diameter ratio. After the electric field is applied, the local electric field will gather at both ends parallel to the electric field direction, which will increase the probability of breakdown behavior. Through the tape casting preparation molding process, the Al2O3 sheet template is oriented in the same direction in the antiferroelectric ceramic material matrix, and then the upper and lower surfaces parallel to the Al2O3 sheet template are polished and gold sprayed to obtain the antiferroelectric ceramic material in which the Al2O3 sheet template is arranged in parallel with the test electrode. The Al2O3 sheet template can effectively disperse the applied electric field in the entire antiferroelectric ceramic material matrix to reduce the uneven distribution of the local electric field, which is conducive to improving the breakdown strength of the antiferroelectric ceramic material, and then improve the energy storage density of the antiferroelectric ceramic material. Since the sheet Al2O3 template is a high insulation material with the characteristics of high withstand voltage breakdown strength, the addition of the Al2O3 sheet template can increase the resistance of the composite material, thereby increasing the number of bound charges and reducing the movement of free charges. In addition, the parallel-arranged Al2O3 flake templates can effectively disperse the applied electric field in the entire antiferroelectric ceramic material matrix due to their large aspect ratio, so as to reduce the uneven distribution of the local electric field. At the same time, when the electric field is applied, the parallel-arranged Al2O3 flake templates in the composite material can form a wider interface barrier, which has an obstructive effect on charge carriers, thereby reducing leakage current and effectively hindering the extension of the electric tree path, which can reduce the growth rate of the electric tree or even stop the growth, thereby avoiding the breakdown behavior of the composite material. All of the above are conducive to improving the breakdown strength of the antiferroelectric ceramic material, and thus improving the energy storage density of the antiferroelectric ceramic material.
[0028] (2) After the sufficient stirring step of the tape casting preparation process, the addition of the second phase Al2O3 flake template is beneficial to improving the breakdown strength of the antiferroelectric ceramic material composite material, thereby improving the energy storage density of the antiferroelectric ceramic material.
[0029] After the sufficient stirring step of the tape casting preparation process, the Al2O3 flake template is evenly distributed in the antiferroelectric ceramic material, and the dielectric constant of Al2O3 is about 10. 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995The dielectric constant of O3 solid solution powder ceramics is about 500, and the dielectric constants of the two are quite different. According to the voltage division theory, when an electric field is applied, the dielectric constant of Al2O3 is low, and more voltage will be gathered on Al2O3, thus forming a local electric field distribution. Al2O3 itself has a high breakdown field strength and can bear a higher electric field strength, so that the voltage that the antiferroelectric ceramic material matrix in the composite material can withstand will also be higher than that of pure ceramics. Therefore, adding the second phase Al2O3 flake template is beneficial to improving the breakdown strength of the antiferroelectric ceramic material composite material, thereby improving the energy storage density of the antiferroelectric ceramic material.
[0030] (3) The Al2O3 flake template exists as a second phase in the antiferroelectric ceramic material composite material, which does not change the antiferroelectric properties of the antiferroelectric ceramic material composite material, so that while obtaining high breakdown strength, the multi-level phase transition characteristics of the antiferroelectric ceramic material matrix ceramic are maintained. Under the induction of high electric field, the polarization strength of the antiferroelectric system of the antiferroelectric ceramic material can be greatly improved due to the antiferroelectric-ferroelectric phase transition. Formula, the polarization intensity P is increased, which can effectively ensure the energy storage density value W rec increase.
[0031] (4) The composition and process of the present invention are simple, easy to operate, have good reproducibility, and the raw materials are cheap and readily available. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1 is the XRD spectrum of the ceramic materials of Examples 1-4 and Comparative Example 1 of the present invention.
[0033] Figure 2 The SEM images of the cross-sections of the ceramic materials of Examples 1-4 and Comparative Example 1 of the present invention are as follows:
[0034] Figure 3 This is the EDS spectrum of Example 1.
[0035] Figure 4 This is a graph showing the variation of the relative dielectric constant of the ceramic materials of Examples 1-4 and Comparative Example 1 of the present invention with temperature.
[0036] Figure 5 These are the hysteresis loops of the ceramic materials of Examples 1-4 of the present invention.
[0037] Figure 6 It is the hysteresis loop of the ceramic material of comparative example 1-13. DETAILED DESCRIPTION
[0038] For ease of understanding, a high energy storage density antiferroelectric ceramic material and a preparation method thereof are described below in conjunction with embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.
[0039] In this embodiment, the reagents and raw materials used are all commercially available Sinopharm reagents unless otherwise specified.
[0040] A high energy storage density antiferroelectric ceramic material with the chemical general formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - x wt% Al2O3, where 0 < x ≤ 0.7, Al2O3 is a flake template of Al2O3. The flake template of Al2O3 is oriented in the same direction in the antiferroelectric ceramic material through a tape casting preparation process and the flake template of Al2O3 is adjusted to be parallel to the test electrode by polishing and spraying gold on the upper and lower surfaces parallel to the flake template of Al2O3.
[0041] Preferably, the chemical general formula is (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - x wt% Al2O3, where 0.1 ≤ x ≤ 0.7, Al2O3 is a flake template of Al2O3. The flake template of Al2O3 is oriented in the same direction in the antiferroelectric ceramic material through a tape casting preparation process and the flake template of Al2O3 is adjusted to be parallel to the test electrode by polishing and spraying gold on the upper and lower surfaces parallel to the flake template of Al2O3.
[0042] A preparation method of a high energy storage density antiferroelectric ceramic material, comprising the following steps:
[0043] S1: According to the stoichiometric ratio of the chemical general formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - x wt% Al2O3, prepare the powder raw materials of PbO, La2O3, ZrO2, and SnO2 in proportion, put the powder raw materials, anhydrous ethanol solvent and yttria - stabilized zirconia bead milling medium into a ball milling tank for ball milling. The mass ratio of the anhydrous ethanol solvent to the powder raw materials is (0.8 - 0.9):1, the mass ratio of the yttria - stabilized zirconia beads to the powder raw materials is (4.5 - 3.5):1, the ball milling speed is 280 - 300 r / min, the ball milling time is 12 - 24 h, then dry and screen to obtain a mixed powder, and calcine the mixed powder in a muffle furnace at 800 °C for 2 h to synthesize (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 solid solution powder, that is, obtain PLZS solid solution powder;
[0044] S2: Add anhydrous ethanol solvent and yttrium-stabilized zirconia bead ball milling medium to the PLZS solid solution powder obtained in step S1 and then perform ball milling. The mass ratio of anhydrous ethanol solvent to PLZS solid solution powder is (0.8-0.9):1, the mass ratio of yttrium-stabilized zirconia bead ball milling medium to PLZS solid solution powder is (4.5-3.5):1, the ball milling speed is 280-300 r / min, the ball milling time is 24-36h, and then dry and sieving to obtain PLZS fine powder.
[0045] S3: Anhydrous ethanol solvent, butanone solvent, triethyl phosphate dispersant, polyvinyl butyral adhesive, dibutyl phthalate plasticizer, and yttrium-stabilized zirconia bead ball milling medium are added to the PLZS fine powder obtained in step S2, and then ball milling is performed. The mass ratio of anhydrous ethanol solvent to PLZS fine powder is (4-5):10, the mass ratio of butanone solvent to PLZS fine powder is (3-4):10, and the mass ratio of triethyl phosphate dispersant to PLZS fine powder is ( 0.2-0.4):10, the mass ratio of polyethanol butyral binder to PLZS fine powder is (0.6-0.7):10, the mass ratio of dibutyl phthalate plasticizer to PLZS fine powder is (0.6-0.7):10, the mass ratio of yttrium stabilized zirconia beads to PLZS fine powder is (4.5-3.5):1, the ball milling speed is 280-300r / min, the ball milling time is 24-36h, and the ceramic slurry is obtained after ball milling;
[0046] S4: Place the ceramic slurry obtained in step S3 in a beaker, add a stirring magnet to the beaker, and then stir according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-xwt% Al2O3 is added in proportion to the Al2O3 flake template prepared by the molten salt method according to patent CN107326432. The radial diameter of the Al2O3 flake template is 9.5μm and the thickness is 0.55μm. The mass of the Al2O3 flake template added is xwt% of the mass of the PLZS fine powder in step S2, and then the beaker is placed in a magnetic stirrer and stirred at a stirring speed of 450-600r / min for 24-36h. After stirring, a mixed slurry is obtained, and the viscosity of the mixed slurry reaches about 1000Pa.S;
[0047] S5: Defoam the mixed slurry obtained in step S4 by stirring and vacuuming with a vacuum defoamer, the vacuum defoaming time is 1-2h, and the stirring speed is 150-350r / min;
[0048] S6: The slurry obtained in step S5 is cast by a manual tape casting machine. According to the document "GN Howatt, RGB Breckenridge, JM Brownlow. Fabrication of Thin Ceramic Sheets for Capacitors. Journal of the American Ceramic Society, 30[8]237-42 (1947)", the Al2O3 sheet template is oriented in the same direction in the high energy storage density antiferroelectric ceramic material matrix through a tape casting preparation process. The casting speed of the manual tape casting machine is 3.5-4cm / min. The obtained ceramic diaphragm has a single layer thickness of 0.07-0.09mm. After drying and cutting, a ceramic diaphragm with a size of 25mm×25mm is obtained;
[0049] S7: The ceramic diaphragms obtained in step S6 are stacked in the same direction according to the Al2O3 sheet template, and then placed in a mold, the ceramic diaphragms are stacked in 20-25 layers, the mold is heated by a heating sleeve, and hot pressed by a manual tablet press, the hot pressing temperature of the manual tablet press is 50-60°C, the hot pressing pressure of the manual tablet press is 20-25Mpa, and the holding time is 10-15min, and then compacted by a cold isostatic press at a pressure of 200-300MPa to obtain a large square ceramic green embryo with a size of 25mm×25mm and a thickness of 1-1.5mm, and finally manually cut to obtain a small square ceramic green embryo with a size of 5mm×5mm and a thickness of 1-1.5mm;
[0050] S8: placing the small square green embryo obtained in step S7 in an Al2O3 crucible, placing the Al2O3 crucible in a muffle furnace for debinding, sintering at 600-650°C for 4-6h, and then sintering at 1170-1200°C for 3-4h to obtain a sintered ceramic sheet with a dense structure;
[0051] S9: The upper and lower surfaces of the sintered ceramic sheet obtained in step S8 parallel to the Al2O3 sheet template are polished to a thickness of 0.1-0.12 mm, then ultrasonically cleaned and dried, and then gold is sprayed on the upper and lower surfaces parallel to the Al2O3 sheet template to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged in parallel.
[0052] The above S3-S8 steps are a casting preparation process, and the PLZS fine powder is added with anhydrous ethanol and butanone solvent, polyvinyl butyral adhesive, triethyl phosphate dispersant and dibutyl phthalate plasticizer and other organic solvents to be ball-milled and mixed evenly, so that the diaphragm after the slurry casting has plasticity. The ball-milled slurry is poured out and placed in a beaker, and a stirring magnet is added in the beaker, and Al2O3 sheet template is added to the beaker, and then the beaker is placed on a magnetic stirrer and stirred. After stirring, after the viscosity of the slurry reaches about 1000Pa.S, the slurry is poured into the defoaming tank of a vacuum defoaming machine, and then placed in the vacuum defoaming machine, defoamed by stirring and vacuumizing, and then cast on a manual casting machine. After this, the Al2O3 sheet template can be obtained in the PLZS matrix ceramic along the same direction oriented composite ceramics. The composite ceramic is then polished and gold-sprayed on the upper and lower surfaces parallel to the Al2O3 sheet template, and finally a ceramic product is obtained in which the Al2O3 sheet template and the test electrode are arranged in parallel.
[0053] Embodiment 1:
[0054] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.3wt%Al2O3, referred to as PLZS-0.3wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.3, Al2O3 is an Al2O3 flake template, the Al2O3 flake template is oriented along the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flake template is regulated to be parallel to the test electrode by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 flake template.
[0055] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0056] S1: According to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995The stoichiometric ratio of O3 -0.3wt% Al2O3 is prepared, and PbO, La2O3, ZrO2, and SnO2 powder raw materials are prepared in proportion. The powder raw materials, anhydrous ethanol solvent and yttrium-stabilized zirconia bead ball milling media are put into a ball mill for ball milling. The mass ratio of anhydrous ethanol solvent to powder raw materials is (0.8-0.9):1, the mass ratio of yttrium-stabilized zirconia beads to powder raw materials is (4.5-3.5):1, the ball milling speed is 280-300r / min, the ball milling time is 12-24h, and then the mixed powder is obtained after drying and sieving. The mixed powder is calcined in a muffle furnace at 800°C for 2h to synthesize (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 solid solution powder, that is, PLZS solid solution powder;
[0057] S2: Add anhydrous ethanol solvent and yttrium-stabilized zirconia bead ball milling medium to the PLZS solid solution powder obtained in step S1 and then perform ball milling. The mass ratio of anhydrous ethanol solvent to PLZS solid solution powder is (0.8-0.9):1, the mass ratio of yttrium-stabilized zirconia bead ball milling medium to PLZS solid solution powder is (4.5-3.5):1, the ball milling speed is 280-300 r / min, the ball milling time is 24-36h, and then dry and sieving to obtain PLZS fine powder.
[0058] S3: Anhydrous ethanol solvent, butanone solvent, triethyl phosphate dispersant, polyvinyl butyral adhesive, dibutyl phthalate plasticizer, and yttrium-stabilized zirconia bead ball milling medium are added to the PLZS fine powder obtained in step S2, and then ball milling is performed. The mass ratio of anhydrous ethanol solvent to PLZS fine powder is (4-5):10, the mass ratio of butanone solvent to PLZS fine powder is (3-4):10, and the mass ratio of triethyl phosphate dispersant to PLZS fine powder is ( 0.2-0.4):10, the mass ratio of polyethanol butyral binder to PLZS fine powder is (0.6-0.7):10, the mass ratio of dibutyl phthalate plasticizer to PLZS fine powder is (0.6-0.7):10, the mass ratio of yttrium stabilized zirconia beads to PLZS fine powder is (4.5-3.5):1, the ball milling speed is 280-300r / min, the ball milling time is 24-36h, and the ceramic slurry is obtained after ball milling;
[0059] S4: Place the ceramic slurry obtained in step S3 in a beaker, add a stirring magnet to the beaker, and then stir according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995The stoichiometric ratio of O3-0.3wt% Al2O3 is added in proportion to the Al2O3 flake template prepared by the molten salt method according to patent CN107326432. The radial diameter of the Al2O3 flake template is 9.5μm and the thickness is 0.55μm. The mass of the Al2O3 flake template added is 0.3% of the mass of the PLZS fine powder in step S2, and then the beaker is placed in a magnetic stirrer and stirred at a stirring speed of 450-600r / min for 24-36h. After stirring, a mixed slurry is obtained, and the viscosity of the mixed slurry reaches about 1000Pa.S;
[0060] S5: Defoam the mixed slurry obtained in step S4 by stirring and vacuuming with a vacuum defoamer, the vacuum defoaming time is 1-2h, and the stirring speed is 150-350r / min;
[0061] S6: The slurry obtained in step S5 is cast by a manual tape casting machine. According to the document "GN Howatt, RGB Breckenridge, JM Brownlow. Fabrication of Thin Ceramic Sheets for Capacitors. Journal of the American Ceramic Society, 30[8]237-42 (1947)", the Al2O3 sheet template is oriented in the same direction in the high energy storage density antiferroelectric ceramic material matrix through a tape casting preparation process. The casting speed of the manual tape casting machine is 3.5-4cm / min. The obtained ceramic diaphragm has a single layer thickness of 0.07-0.09mm. After drying and cutting, a ceramic diaphragm with a size of 25mm×25mm is obtained;
[0062] S7: The ceramic diaphragms obtained in step S6 are stacked in the same direction according to the Al2O3 sheet template, and then placed in a mold, the ceramic diaphragms are stacked in 20-25 layers, the mold is heated by a heating sleeve, and hot pressed by a manual tablet press, the hot pressing temperature of the manual tablet press is 50-60°C, the hot pressing pressure of the manual tablet press is 20-25Mpa, and the holding time is 10-15min, and then compacted by a cold isostatic press at a pressure of 200-300MPa to obtain a large square ceramic green embryo with a size of 25mm×25mm and a thickness of 1-1.5mm, and finally manually cut to obtain a small square ceramic green embryo with a size of 5mm×5mm and a thickness of 1-1.5mm;
[0063] S8: placing the small square green embryo obtained in step S7 in an Al2O3 crucible, placing the Al2O3 crucible in a muffle furnace for debinding, sintering at 600-650°C for 4-6h, and then sintering at 1170-1200°C for 3-4h to obtain a sintered ceramic sheet with a dense structure;
[0064] S9: The upper and lower surfaces of the sintered ceramic sheet obtained in step S8 parallel to the Al2O3 sheet template are polished to a thickness of 0.1-0.12 mm, then ultrasonically cleaned and dried, and then gold is sprayed on the upper and lower surfaces parallel to the Al2O3 sheet template to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged in parallel.
[0065] Embodiment 2:
[0066] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.1wt%Al2O3, referred to as PLZS-0.1wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.1, Al2O3 is an Al2O3 flake template, the Al2O3 flake template is oriented along the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flake template is regulated to be parallel to the test electrode by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 flake template.
[0067] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0068] The difference from Example 1 is that in step S4, the mass of the Al2O3 flake template added is 0.1% of the mass of the PLZS fine powder in step S2.
[0069] Embodiment 3:
[0070] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.5wt%Al2O3, referred to as PLZS-0.5wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995In O3-xwt%Al2O3, x=0.5, Al2O3 is an Al2O3 flake template, the Al2O3 flake template is oriented along the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flake template is regulated to be parallel to the test electrode by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 flake template.
[0071] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0072] The difference from Example 1 is that in step S4, the mass of the Al2O3 flake template added is 0.5% of the mass of the PLZS fine powder in step S2.
[0073] Embodiment 4:
[0074] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.7wt%Al2O3, referred to as PLZS-0.7wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.7, Al2O3 is an Al2O3 flake template, the Al2O3 flake template is oriented along the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flake template is regulated to be parallel to the test electrode by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 flake template.
[0075] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0076] The difference from Example 1 is that in step S4, the mass of the Al2O3 flake template added is 0.7% of the mass of the PLZS fine powder in step S2.
[0077] Comparative Example 1:
[0078] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3, abbreviated as PLZS.
[0079] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0080] The difference from Example 1 is that after step S3, step S4 is not performed and step S5 is performed directly.
[0081] Comparative Example 2:
[0082] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.3wt%Al2O3, referred to as PLZS-0.3wt%Al2O3, where the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.3, Al2O3 is granular, and the granular Al2O3 is randomly arranged in the antiferroelectric ceramic material.
[0083] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0084] The difference from Example 1 is that in step S4, the ceramic slurry obtained in step S3 is placed in a beaker, a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-0.3wt% Al2O3 is adjusted, and granular Al2O3 is added in proportion, and the mass of the added granular Al2O3 is 0.3% of the mass of the PLZS fine powder in step S2.
[0085] Comparative Example 3:
[0086] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.1wt%Al2O3, referred to as PLZS-0.1wt%Al2O3, where the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.1, Al2O3 is granular, and the granular Al2O3 is randomly arranged in the antiferroelectric ceramic material.
[0087] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0088] The difference from Example 2 is that in step S4, the ceramic slurry obtained in step S3 is placed in a beaker, a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-0.1wt% Al2O3 is adjusted, and granular Al2O3 is added in proportion, and the mass of the added granular Al2O3 is 0.1% of the mass of the PLZS fine powder in step S2.
[0089] Comparative Example 4:
[0090] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.5wt%Al2O3, referred to as PLZS-0.5wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.5, Al2O3 is granular, and the granular Al2O3 is randomly arranged in the antiferroelectric ceramic material.
[0091] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0092] The difference from Example 3 is that in step S4, the ceramic slurry obtained in step S3 is placed in a beaker, a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-0.5wt% Al2O3 is adjusted, and granular Al2O3 is added in proportion, and the mass of the added granular Al2O3 is 0.5% of the mass of the PLZS fine powder in step S2.
[0093] Comparative Example 5:
[0094] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 )0.995 O3-0.7wt%Al2O3, referred to as PLZS-0.7wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.7, Al2O3 is granular, and the granular Al2O3 is randomly arranged in the antiferroelectric ceramic material.
[0095] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0096] The difference from Example 4 is that in step S4, the ceramic slurry obtained in step S3 is placed in a beaker, a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-0.7wt% Al2O3 is adjusted, and granular Al2O3 is added in proportion, and the mass of the added granular Al2O3 is 0.7% of the mass of the PLZS fine powder in step S2.
[0097] Comparative Example 6:
[0098] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.3wt%Al2O3, referred to as PLZS-0.3wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.3, Al2O3 is a flake template, and the Al2O3 flake template is randomly arranged in the antiferroelectric ceramic material through a solid phase preparation process.
[0099] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0100] The difference from Example 1 is that the steps S3-S8 in Example 1 adopt the tape casting preparation process, while the solid phase preparation process is adopted from step S3 onwards in Comparative Example 6. The specific differences from step S3 onwards and Example 1 are as follows:
[0101] S3: Put the PLZS fine powder obtained in step S2, Al2O3 flake template, anhydrous ethanol solvent and stirring magnet into a beaker, add Al2O3 flake template with a mass of 0.3% of the mass of PLZS fine powder in step S2, and stir in a magnetic stirrer at a stirring speed of 450-600 r / min for 24-36 h to obtain a mixed slurry;
[0102] S4: the mixed slurry obtained in step S3 is placed in an oven for drying to obtain a mixed powder;
[0103] S5: The mixed powder obtained in step S4 is pressed into a disc-shaped ceramic green body with a diameter of 6 mm and a thickness of 1-1.5 mm by cold isostatic pressing at a pressure of 200-300 MPa;
[0104] S6: placing the ceramic green body obtained in step S5 in an Al2O3 crucible, and then placing the Al2O3 crucible in a muffle furnace, and sintering at 1170-1200°C for 3-4h to obtain a sintered ceramic sheet with a dense structure;
[0105] S7: polishing the sintered ceramic sheet obtained in step S6 to a thickness of 0.1-0.12 mm, ultrasonically cleaning and drying, and spraying gold on the upper and lower surfaces to obtain a finished antiferroelectric ceramic material with high energy storage density.
[0106] Comparative Example 7:
[0107] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.1wt%Al2O3, referred to as PLZS-0.1wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.1, Al2O3 is a flake template, and the Al2O3 flake template is randomly arranged in the antiferroelectric ceramic material through a solid phase preparation process.
[0108] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0109] The difference from Example 2 is that: in Example 2, steps S3-S8 adopt the tape casting preparation process, and in Comparative Example 7, starting from step S3, the solid phase preparation process is adopted. The difference from step S3 to Comparative Example 6 is as follows:
[0110] S3: The mass of the Al2O3 flake template added is 0.1% of the mass of the PLZS fine powder in step S2.
[0111] Comparative Example 8:
[0112] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.5wt%Al2O3, referred to as PLZS-0.5wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.5, Al2O3 is a flake template, and the Al2O3 flake template is randomly arranged in the antiferroelectric ceramic material through a solid phase preparation process.
[0113] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0114] The difference from Example 3 is that the steps S3-S8 in Example 3 adopt the tape casting preparation process, while the solid phase preparation process is adopted from step S3 onwards in Comparative Example 8. The difference from step S3 onwards from Comparative Example 6 is as follows:
[0115] S3: The mass of the Al2O3 flake template added is 0.5% of the mass of the PLZS fine powder in step S2.
[0116] Comparative Example 9:
[0117] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.7wt%Al2O3, referred to as PLZS-0.7wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt% Al2O3, x=0.7, Al2O3 is a flake template, and the Al2O3 flake template is randomly arranged in the antiferroelectric ceramic material through a solid phase preparation process.
[0118] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0119] The difference from Example 4 is that the steps S3-S8 in Example 4 adopt the tape casting preparation process, while the solid phase preparation process is adopted from step S3 onwards in Comparative Example 9. The difference from step S3 onwards from Comparative Example 6 is as follows:
[0120] S3: The mass of the Al2O3 flake template added is 0.7% of the mass of the PLZS fine powder in step S2.
[0121] Comparative Example 10:
[0122] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.3wt%Al2O3, referred to as PLZS-0.3wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.3, Al2O3 is a flake template, and the Al2O3 flake template is oriented in the antiferroelectric ceramic material and perpendicular to the test electrode.
[0123] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0124] The difference from Example 1 is that in step S9, the surface of the sintered ceramic sheet obtained in step S8 that is perpendicular to the Al2O3 sheet template is linearly cut to a thickness of 1-1.5 mm, and then the cut section is polished up and down, and then ultrasonically cleaned and dried, and gold is sprayed on the upper and lower surfaces to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged vertically.
[0125] Comparative Example 11:
[0126] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.1wt%Al2O3, referred to as PLZS-0.1wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995In O3-xwt%Al2O3, x=0.1, Al2O3 is a flake template, and the Al2O3 flake template is oriented in the antiferroelectric ceramic material and perpendicular to the test electrode.
[0127] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0128] The difference from Example 2 is that in step S9, the surface of the sintered ceramic sheet obtained in step S8 that is perpendicular to the Al2O3 sheet template is linearly cut to a thickness of 1-1.5 mm, and then the cut section is polished up and down, and then ultrasonically cleaned and dried, and gold is sprayed on the upper and lower surfaces to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged vertically.
[0129] Comparative Example 12:
[0130] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-0.5wt%Al2O3, referred to as PLZS-0.5wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.5, Al2O3 is a flake template, and the Al2O3 flake template is oriented in the antiferroelectric ceramic material and perpendicular to the test electrode.
[0131] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0132] The difference from Example 3 is that in step S9, the surface of the sintered ceramic sheet obtained in step S8 that is perpendicular to the Al2O3 sheet template is linearly cut to a thickness of 1-1.5 mm, and then the cut section is polished up and down, and then ultrasonically cleaned and dried, and gold is sprayed on the upper and lower surfaces to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged vertically.
[0133] Comparative Example 13:
[0134] A high energy storage density antiferroelectric ceramic material with a general chemical formula of (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995O3-0.7wt%Al2O3, referred to as PLZS-0.7wt%Al2O3, wherein the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 In O3-xwt%Al2O3, x=0.7, Al2O3 is a flake template, and the Al2O3 flake template is oriented in the antiferroelectric ceramic material and perpendicular to the test electrode.
[0135] A method for preparing an antiferroelectric ceramic material with high energy storage density comprises the following steps:
[0136] The difference from Example 4 is that in step S9, the surface of the sintered ceramic sheet obtained in step S8 that is perpendicular to the Al2O3 sheet template is linearly cut to a thickness of 1-1.5 mm, and then the cut section is polished up and down, and then ultrasonically cleaned and dried, and gold is sprayed on the upper and lower surfaces to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged vertically.
[0137] Experiment 1
[0138] The phase structures of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 were measured using Smartlab 3KW produced by Rigaku. Figure 1 The XRD patterns of the ceramic materials prepared in Examples 1-4 and Comparative Example 1 are as follows: Figure 1 It can be seen that the prepared ceramic materials are all pure phases. It may be because the amount of added Al2O3 is too small and no Al2O3 peak is detected.
[0139] Experiment 2
[0140] The cross sections of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 were tested using Phenom ProX produced by Phenom of the Netherlands. Figure 2 The SEM images of the cross sections of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 are as follows: Figure 2 Figures a and b are SEM images of Comparative Example 1, Example 2, Example 1, Example 3 and Example 4. In the SEM image of Comparative Example 1, only pure matrix ceramic grains are observed. Compared with the pure matrix ceramic of Comparative Example 1, parallel-arranged flake templates can be clearly observed in Examples 1 to 4 (in the circle), and as the content of Al2O3 flake templates in Example 2, Example 1, Example 3 and Example 4 increases successively, the number of observed flake templates also gradually increases.
[0141] In order to further confirm that the flake template is Al2O3, Figure 3 This is the EDS spectrum of the ceramic material of Example 1. Through the SEM picture ( Figure 3 a) and element comparison ( Figure 3 b) Analysis revealed that the Al element was concentrated in the flake template, while the Pb, La, Zr, Sn and O elements were evenly distributed in the matrix ceramic, indicating that the added Al2O3 flake template was not dissolved into the matrix ceramic, but existed as a second phase in the composite ceramic.
[0142] Experiment 3
[0143] The dielectric properties of the ceramic materials prepared in Examples 1 to 4 and Comparative Example 1 were tested using E4990A produced by Keysight, USA, to analyze the changing pattern of the influence of Al2O3 on the dielectric properties of the ceramic materials. Figure 4 The relative dielectric constant (ε) of the ceramic materials prepared in Examples 1-4 and Comparative Example 1 r ) changes with temperature. It can be seen that adding a small amount of Al2O3 has no effect on the dielectric properties of the composite material, indicating that adding Al2O3 will not significantly change the electrical properties of the ceramic material.
[0144] Experiment 4
[0145] The ferroelectric properties of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1-13 were tested using a TF 3000E ferroelectric analyzer produced by aixACCT of Germany. Figure 5 is the hysteresis loop of the ceramic material prepared in Example 1-4 at a test frequency of 10 Hz, Figure 6 1-13 is the hysteresis loop of the ceramic material prepared in Example 1-13 at a test frequency of 10 Hz. It can be seen from the figure that the hysteresis loops of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1-13 all have multi-level phase transitions. The Al2O3 flake template exists in the antiferroelectric ceramic material composite material as a second phase, which will not change the antiferroelectric properties of the lead-based ceramic, so that while obtaining high breakdown strength, the multi-level phase transition characteristics of the antiferroelectric ceramic material matrix are maintained. The P of the ceramic material r The values (residual polarization intensity) are small. Formula, P r The value is small, which can effectively ensure the energy storage density value W rec In Example 1-4, due to the antiferroelectric-ferroelectric phase transition under the induction of high electric field, the polarization intensity P can be greatly improved.
[0146] Formula, the polarization intensity P is increased, which can effectively ensure the energy storage density value W rec increase.
[0147] Table 1 shows the ferroelectric performance parameters of the ceramic materials prepared in Examples 1-4 and Comparative Examples 1-13. The energy storage density and energy storage efficiency can be calculated according to the following formula:
[0148]
[0149] Among them, W total is the total energy storage density; W rec is the releasable energy storage density; η is the energy storage efficiency; E is the external electric field strength; P is the polarization strength; P r is the residual polarization intensity; P max is the maximum polarization value. The breakdown field strength E of Examples 1-4 b The range is 480-560kV / cm, and the energy storage density value is W rec The value is between 10.31-13.5J / cm 3 As shown in Table 1, as the content of flaky Al2O3 added gradually increases in Example 2, Example 1, Example 3, and Example 4, the breakdown strength gradually increases, indicating that adding an Al2O3 flaky template and making it parallel to the test electrode can improve the breakdown strength of the ceramic material, thereby improving the energy storage density of the antiferroelectric ceramic material.
[0150] However, since Al2O3 is a linear dielectric material, its polarization strength is relatively low. Therefore, in Example 2, Example 1, Example 3, and Example 4, as the Al2O3 sheet template increases, the polarization strength of the composite material increases first and then decreases. rec The energy storage density also increases first and then decreases. The maximum energy storage density of 13.5 J / cm2 is obtained in the PLZS-0.3 wt% Al2O3 ceramic material prepared in Example 1. 3 Therefore, x in the present invention cannot be too low or too high. If x is too low, such as 0, the breakdown strength of the ceramic material of the present invention is limited and the energy storage density is too low. If x is too high, such as greater than 0.7, the maximum polarization strength of the ceramic material of the present invention will be reduced, resulting in reduced energy storage density and efficiency.
[0151] The breakdown strength of the PLZS pure matrix ceramic material prepared in Comparative Example 1 is relatively small, which is 390 kV / cm. rec The energy storage density is 8.74 J / cm 3The Al2O3 added to the ceramic materials prepared in Comparative Examples 2-5 is in granular form and randomly arranged in the composite antiferroelectric ceramic material. Compared with the pure matrix ceramic of Comparative Example 1, the ceramic materials prepared in Comparative Examples 2-5 can increase the breakdown electric field of the composite antiferroelectric ceramic material from 390kV / cm to 450kV / cm. When the Al2O3 flake templates in the ceramic materials prepared in Comparative Examples 6-9 are randomly arranged in the composite antiferroelectric ceramic material, the breakdown electric field of the composite antiferroelectric ceramic material is also improved compared with the pure matrix ceramic material, which is similar to the ceramic material prepared in Comparative Example 2, ranging from 410-440kV / cm. When the Al2O3 flake templates in Comparative Examples 10-13 are arranged vertically to the test electrode, their breakdown electric field does not increase but decreases, and is even lower than that of the pure matrix ceramic material. The above shows that the morphology and arrangement of Al2O3 in the composite antiferroelectric ceramic material have an important influence on the polarization strength of the composite antiferroelectric ceramic material, thereby affecting the energy storage density of the composite antiferroelectric ceramic material. When the reinforcing phase is an Al2O3 flake template, the energy storage density of the composite antiferroelectric ceramic material can be increased by up to about 50% when the Al2O3 flake template is oriented and arranged in parallel with the test electrode. It can be seen that changing the morphology and arrangement of the reinforcing phase Al2O3 is an effective way to significantly improve the breakdown electric field and energy storage density of the composite antiferroelectric ceramic material. Examples 1 to 4 prove that when the reinforcing phase Al2O3 is added as a flake template and the flake template is parallel to the test electrode, the enhancement effect of the breakdown strength of the antiferroelectric ceramic material is the most obvious, for the following reasons:
[0152] (1) The Al2O3 sheet template is first prepared by a molten salt method and then tape-casted (also called scraper forming) by a tape-casting preparation process. The tape-casting preparation process can make the Al2O3 sheet template oriented in the same direction in the antiferroelectric ceramic material matrix. Then, by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 sheet template, an antiferroelectric ceramic material in which the Al2O3 sheet template and the test electrode are arranged in parallel is obtained, so that the Al2O3 sheet template effectively disperses the applied electric field in the entire antiferroelectric ceramic material matrix to reduce the uneven distribution of the local electric field, which is beneficial to improve the breakdown strength of the antiferroelectric ceramic material, and then improve the energy storage density of the antiferroelectric ceramic material.
[0153] The existing granular Al2O3 reinforcement phase has a small aspect ratio. After the electric field is applied, the local electric field will gather at both ends parallel to the electric field direction, which will increase the probability of breakdown behavior. Through the tape casting preparation molding process, the Al2O3 sheet template is oriented in the same direction in the antiferroelectric ceramic material matrix, and then the upper and lower surfaces parallel to the Al2O3 sheet template are polished and gold sprayed to obtain the antiferroelectric ceramic material in which the Al2O3 sheet template is arranged in parallel with the test electrode. Since the sheet Al2O3 template is a high insulation material with high withstand voltage breakdown strength, the addition of the Al2O3 sheet template can increase the resistance of the composite material, thereby increasing the number of bound charges and reducing the movement of free charges. In addition, the parallel-arranged Al2O3 flake templates can effectively disperse the applied electric field in the entire antiferroelectric ceramic material matrix due to their large aspect ratio, so as to reduce the uneven distribution of the local electric field. At the same time, when the electric field is applied, the parallel-arranged Al2O3 flake templates in the composite material can form a wider interface barrier, which has an obstructive effect on charge carriers, thereby reducing leakage current and effectively hindering the extension of the electric tree path, which can reduce the growth rate of the electric tree or even stop the growth, thereby avoiding the breakdown behavior of the composite material. All of the above are conducive to improving the breakdown strength of the antiferroelectric ceramic material, and thus improving the energy storage density of the antiferroelectric ceramic material.
[0154] (2) After the sufficient stirring step of the tape casting preparation process, the addition of the second phase Al2O3 flake template is beneficial to improving the breakdown strength of the antiferroelectric ceramic material composite material, thereby improving the energy storage density of the antiferroelectric ceramic material.
[0155] After the sufficient stirring step of the tape casting preparation process, the Al2O3 flake template is evenly distributed in the antiferroelectric ceramic material, and the dielectric constant of Al2O3 is about 10. 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The dielectric constant of O3 solid solution powder ceramics is about 500, and the dielectric constants of the two are quite different. According to the voltage division theory, when an electric field is applied, the dielectric constant of Al2O3 is low, and more voltage will be gathered on Al2O3, thus forming a local electric field distribution. Al2O3 itself has a high breakdown field strength and can bear a higher electric field strength, so that the voltage that the antiferroelectric ceramic material matrix in the composite material can withstand will also be higher than that of pure ceramics. Therefore, adding the second phase Al2O3 flake template is beneficial to improving the breakdown strength of the antiferroelectric ceramic material composite material, thereby improving the energy storage density of the antiferroelectric ceramic material.
[0156] (3) The Al2O3 flake template exists as a second phase in the antiferroelectric ceramic material composite material, which does not change the antiferroelectric properties of the antiferroelectric ceramic material composite material, so that while obtaining high breakdown strength, the multi-level phase transition characteristics of the antiferroelectric ceramic material matrix ceramic are maintained. Under the induction of high electric field, the polarization strength of the antiferroelectric system of the antiferroelectric ceramic material can be greatly improved due to the antiferroelectric-ferroelectric phase transition. Formula, the polarization intensity P is increased, which can effectively ensure the energy storage density value W rec increase.
[0157] Table 1
[0158]
[0159]
[0160] In addition, only some exemplary embodiments of the present invention are described above by way of illustration. It is undoubted that, for those skilled in the art, the described embodiments can be modified in various ways without departing from the spirit and scope of the present invention. Therefore, the above drawings and descriptions are illustrative in nature and should not be construed as limiting the scope of protection of the claims of the present invention.
Claims
1. A high energy storage density antiferroelectric ceramic material, characterized in that: The chemical general formula is (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 - xwt%Al2O3, where 0 < x ≤ 0.
7. The Al2O3 is a flaky template, and the Al2O3 flaky template is oriented in the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 flaky template is adjusted to be parallel to the test electrode by polishing and sputtering gold on the upper and lower surfaces parallel to the Al2O3 flaky template.
2. A high energy storage density antiferroelectric ceramic material, characterized in that: The general chemical formula is (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3-xwt%Al2O3, wherein 0.1≤x≤0.7, the Al2O3 is a sheet template, the Al2O3 sheet template is oriented along the same direction in the antiferroelectric ceramic material through a tape casting preparation process, and the Al2O3 sheet template is regulated to be parallel to the test electrode by polishing and gold spraying on the upper and lower surfaces parallel to the Al2O3 sheet template.
3. A method for preparing a high energy storage density antiferroelectric ceramic material according to claim 1 or 2, comprising the following steps: S1: According to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-xwt%Al2O3 is prepared according to the proportion of PbO, La2O3, ZrO2, SnO2 powder raw materials, the powder raw materials, anhydrous ethanol solvent and yttrium-stabilized zirconia bead ball milling medium are put into a ball mill, and then dried and sieved to obtain a mixed powder, and the mixed powder is calcined in a high-temperature furnace to synthesize (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 O3 solid solution powder, that is, PLZS solid solution powder; S2: adding anhydrous ethanol solvent and yttrium-stabilized zirconia bead ball milling medium to the PLZS solid solution powder obtained in step S1, and then ball milling, drying, and sieving to obtain PLZS fine powder; S3: adding anhydrous ethanol solvent, butanone solvent, triethyl phosphate dispersant, polybutyral binder, dibutyl phthalate plasticizer, and yttrium-stabilized zirconia bead ball milling medium to the PLZS fine powder obtained in step S2, and then ball milling to obtain a ceramic slurry; S4: In the ceramic slurry obtained in step S3, according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-xwt%Al2O3 is added with Al2O3 flake template in proportion, and then stirred in a magnetic stirrer to obtain a mixed slurry; S5: Degassing the mixed slurry obtained in step S4 by stirring and vacuuming using a vacuum degassing machine; S6: casting the mixed slurry obtained in step S5 by a manual casting machine, so that the Al2O3 sheet template is oriented in the same direction in the high energy storage density antiferroelectric ceramic material matrix by casting, and then drying and cutting to obtain a ceramic diaphragm; S7: Laminating the ceramic diaphragm obtained in step S6 in a high energy storage density antiferroelectric ceramic material matrix according to an Al2O3 sheet template and placing it in a mold, heating the mold by a heating sleeve, hot pressing by a manual tablet press, compacting by a cold isostatic press, and then manually cutting to obtain a ceramic green embryo; S8: placing the ceramic green body obtained in step S7 in a muffle furnace for debinding and sintering to obtain a sintered ceramic sheet; S9: polishing and ultrasonically cleaning the upper and lower surfaces of the sintered ceramic sheet obtained in step S8 that are parallel to the Al2O3 sheet template, and drying them, spraying gold on the upper and lower surfaces that are parallel to the Al2O3 sheet template, to obtain a high energy storage density antiferroelectric ceramic material product in which the Al2O3 sheet template and the test electrode are arranged in parallel.
4. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the step S7, the ceramic diaphragms obtained in the step S6 are stacked in the same direction according to the Al2O3 sheet template and placed in a mold. The mold is heated by a heating sleeve, hot pressed by a manual tablet press, compacted by a cold isostatic press, and then manually cut to obtain a ceramic green body.
5. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the step S4, the ceramic slurry obtained in the step S3 is placed in a beaker, and a stirring magnet is added to the beaker, and then the ceramic slurry is stirred according to the chemical formula (Pb 0.98 La 0.02 )(Zr 0.7 Sn 0.3 ) 0.995 The stoichiometric ratio of O3-xwt%Al2O3 is prepared, and Al2O3 flake template is added in proportion. The mass of the Al2O3 flake template added is xwt% of the mass of the PLZS fine powder in step S2. Then the beaker is placed in a magnetic stirrer and stirred at a speed of 450-600r / min and a stirring time of 24-36h to obtain a mixed slurry.
6. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the S1 step, the mass ratio of the anhydrous ethanol solvent to the powder raw material is (0.8-0.9):1, the mass ratio of the yttrium-stabilized zirconia beads to the powder raw material is (4.5-3.5):1, the ball mill speed is 280-300 r / min, the ball milling time is 12-24 h, and then the mixed powder is obtained after drying and sieving. The mixed powder is calcined in a muffle furnace at 800° C. for 2 h to synthesize the PLZS solid solution powder.
7. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the S2 step, the mass ratio of the anhydrous ethanol solvent to the PLZS solid solution powder is (0.8-0.9):1, the mass ratio of the yttrium-stabilized zirconia bead ball milling medium to the PLZS solid solution powder is (4.5-3.5):1, the ball milling speed is 280-300 r / min, the ball milling time is 24-36h, and the PLZS fine powder is obtained after drying and sieving.
8. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the S3 step, the mass ratio of the anhydrous ethanol solvent to the PLZS fine powder is (4-5):10, the mass ratio of the butanone solvent to the PLZS fine powder is (3-4):10, the mass ratio of the triethyl phosphate dispersant to the PLZS fine powder is (0.2-0.4):10, the mass ratio of the polyethanol butyral adhesive to the PLZS fine powder is (0.6-0.7):10, the mass ratio of the dibutyl phthalate plasticizer to the PLZS fine powder is (0.6-0.7):10, the mass ratio of the yttrium stabilized zirconia beads to the PLZS fine powder is (4.5-3.5):1, the ball milling speed is 280-300r / min, and the ball milling time is 24-36h.
9. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the step S4, the mass of the Al2O3 flake template added is (0.1-0.7)% of the mass of the PLZS fine powder in the step S2, the stirring speed of the magnetic stirrer is 450-600 r / min, and the stirring time of the magnetic stirrer is 24-36 h.
10. The method for preparing a high energy storage density antiferroelectric ceramic material according to claim 3, characterized in that: In the step S5, the defoaming time of the vacuum defoamer is 1-2 hours, and the stirring speed is 150-350 r / min.
Citation Information
Patent Citations
PLZT / aluminum oxide composite ceramic material and preparation method thereof
CN107129301A
High-energy-storage lead zirconate-based antiferroelectric multilayer ceramic capacitor and preparation method thereof
CN111574198A
Anti-ferroelectric energy storage ceramic with high fatigue resistance, low electric field and high energy storage density as well as preparation method and application of anti-ferroelectric energy storage ceramic
CN116102352A
Sodium niobate-based lead-free antiferroelectric ceramic material with typical double ferroelectric hysteresis loops and preparation method of sodium niobate-based lead-free antiferroelectric ceramic material
CN116332643A
Method for preparing polycrystal texture ceramic material
CN1850725A
Cited By
Ordered ferroelectric composite ceramic with high energy storage density and high temperature stability
CN121651921A